1991
DOI: 10.1007/s0054010050142
|View full text |Cite
|
Sign up to set email alerts
|

Accidental extubations during respiratory management in a children’s hospital

Abstract: An investigation was conducted on the frequency of accidental extubations at Shizuoka Children's Hospital during the past 12 years. The study was performed on 150 randomly selected patients who received respiratory support for more than 24 hr. Fifteen accidental extubations occurred in 9 patients. Most of them (87%) occurred in the neonatal intensive care unit (NICU), and the rate was 1 per 54 days of intubation. The time at which these accidents happened varied, although they were more common during the day-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Brown 11 found that UE rate was higher in neonates Ͻ 1,500 g than in neonates Ͼ 1,500 g (42% vs 23%, P Ͻ .04). Likewise, Horimoto et al 14 found a higher UE rate in infants Ͻ 2,500 g (87%). On the other hand, 3 studies 1,12,17 showed no difference in weight between UE infants and controls.…”
Section: Risk Factors Associated With Unplanned Extubationmentioning
confidence: 85%
See 2 more Smart Citations
“…Brown 11 found that UE rate was higher in neonates Ͻ 1,500 g than in neonates Ͼ 1,500 g (42% vs 23%, P Ͻ .04). Likewise, Horimoto et al 14 found a higher UE rate in infants Ͻ 2,500 g (87%). On the other hand, 3 studies 1,12,17 showed no difference in weight between UE infants and controls.…”
Section: Risk Factors Associated With Unplanned Extubationmentioning
confidence: 85%
“…Fifteen of these studies met the inclusion criteria. 1,3,5,[9][10][11][12][13][14][15][16][17][18][19][20] Of the 15 studies reviewed, 11 were prospective cohort studies. 3,[10][11][12][13][15][16][17][18][19][20] 3 were retrospective cohort studies, 1,9,14 and 1 was a retrospective and prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,5,7,8 Compared with data from PICUs, unplanned extubations in neonatal patients occur 2 to 3 times more frequently. 9 Potential reasons for this increased incidence include longer duration of intubation, shorter length of the trachea in neonates compared with older children, the use of uncuffed endotracheal tubes in neonates, and less routine use of sedation and muscle relaxation, as well as time spent out of bed while being held by parents. Factors that contribute to unplanned extubations include method of fixation of endotracheal tubes; procedures such as weighing and suctioning; and agitation of the patient, resulting in rapid movement of the head.…”
mentioning
confidence: 99%
“…UEs result in high rates of bradycardia, hypoxemia, chest compressions, 1 and reintubation. 2,3 Further, intubation associated adverse events are more common when intubation courses follow an UE than during intubations for other indications.…”
mentioning
confidence: 99%